PENGARUH KAPASITAS OPERASI, PERTUMBUHAN PENJUALAN, DAN MODAL INTELEKTUAL TERHADAP FINANCIAL DISTRESS - Andini Thalita Maulida Irawan, (2022)
This study aims to examine the effect of operating capacity, sales growth, and intellectual capital on financial distress. This study uses a quantitative approach with a population of property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2017 - 2021. The sample used in this study was determined by purposive sampling which resulted in 37 companies and a total of 148 observations. Multiple regression analysis was used to test the hypothesis of this study. by using STATA. This study obtained the results, (1) there is no significant effect between operating capacity on financial distress, (2) there is no significant effect between sales growth on financial distress, (3) there is no significant effect between intellectual capital on financial distress.